Konseling Kelompok Berbasis Hadits Untuk Mengatasi Emosi Marah Mahasiswa - Zhila Jannati; Muhammad Randicha Hamandia (Bulletin of Counseling and Psychotherapy, 2021)
Angry emotions are things that cannot be avoided by humans. It can change the atmosphere for the better or for the worse. The negative emotions of anger are disliked and not condoned by Islam. The purpose of this study was to determine how hadith-based group counseling in dealing with angry emotions in Islamic Guidance and Counseling Study Program students, Faculty of Da'wah and Communication, Raden Fatah State Islamic University, Palembang. The method used in this research is a qualitative research method. The subjects in this study were eight students from the Islamic Counseling and Counseling Study Program, the Faculty of Da'wah and Communication, Raden Fatah State Islamic University, Palembang. The techniques used in collecting research data are interview techniques, observation techniques, and documentation techniques. The data analysis used in this research is descriptive qualitative data analysis. The results of this study indicate that (1) hadith-based group counseling carried out by the researcher through four stages, namely the formation stage, the intermediate stage, the activity stage and the termination stage; and (2) angry emotions experienced by students which include swelling of the veins and veins, red face and eyes, wrinkled face and forehead forming patterns, as well as acts of aggression, both verbal and non-verbal, can be overcome. So, it can be concluded that hadith-based group counseling can be one of the right ways to deal with angry emotions in students